Modeling and Optimising the Growth of Lasiodiplodia theobromae During Gathotan Fermentation - UMI PURWANDARI; NOVIA NAVA; DARIMIYYA HIDAYATI (Microbiology Indonesia, 2014)
Gathotan is fungal fermented cassava, and a raw material for a Javanese snack called ‘gathot’. This type of food is now hardly to find, and the process of making gathotan is relatively lack of process control, leads to failure in process. To make gathotan, peeled cassava tubers are left on the ground or roof for several weeks or months until they become black inside an important characteristic of gathotan. This work aims to improve gathotan fermentation by optimizing fermentation process. The effect of incubation temperature and time, inoculum level, soaking time, and drying, on the growth of Lasiodiplodia theobromae, the main gathotan fungus, in cassava tubers was studied. Experimental design was set up according to response surface methodology. Five parameters measured were pH, titratable acidity, and fungal growth. Results showed that incubation temperature affected pH in linear (P<0.01) and quadratic functions (P<0.05). Titratable acidity was not affected by any treatment. Fungal growth was significantly affected by incubation time (P<0.01) or inoculum level (P<0.05), and interaction of several factors: incubation time and incubation temperature (P<0.05) or drying time (P<0.01). Optimization model indicated that incubation temperature at 34.5°C for 2.4 days, soaking for 26.4 hours, drying time of 3.7 hours at 40°C, and inoculum level of 2% resulted in maximum growth of L. theobromae in gathotan.